Manajemen Kepala Sekolah untuk Meningkatkan Motivasi Kinerja Guru di Sekolah Dasar: Principal Management to Improve Teacher Performance Motivation in Elementary Schools - Oktiviani Ciptanti; Saryanto Saryanto; Rejokirono Rejokirono (ITScience (Information Technology and Science), 2024)
Teachers play a vital role in the education system because they are the ones who are actually responsible for educating students in the classroom. To a large extent, student achievement and teacher satisfaction determine the quality of education. The quality of learning and student learning outcomes are directly influenced by the level of motivation of instructors, which in turn influences their level of enthusiasm when carrying out their duties. With this study, we will better understand how the principals of Tunjungseto Elementary School can inspire their teachers to do their best work. The primary methods of qualitative data collection for this study were interviews, participant observation, and written notes. The study showed that the involvement of the principal in providing ongoing guidance, incentives, and support has a significant impact on the growth of teacher motivation to perform well. Good principals know what they are doing when it comes to encouraging professional development for teachers and cultivating a fun workplace. Motivating teachers to do their best work is an area where principals can make a big difference. To foster an atmosphere that supports teacher professional development, principals must offer clear guidance, inspiration, and ongoing support. If para-administrators are successful in making teachers feel valued and supported in their work, it will show in their motivation and performance in the classroom. How effective principals are in inspiring their staff to perform well depends on a number of factors, including consistent and clear communication, support from management, and adequate resources. Schools with principals who can foster an environment of open communication and who are willing to support improvements in school facilities tend to be happier.